ChemInform Abstract: Au(I)—N‐Heterocyclic Carbene Complex‐Catalyzed Synthesis of 1‐Substituted Benzo[b][1, 4]diazepines from N‐Substituted O‐Phenylenediamines and Terminal Alkynes. Issue 30 (29th July 2014) - Guo, Pei; Zeng, Xiaoming; Chen, Si; Luo, Meiming
Abstract A simple procedure is developed to synthesize benzo[b][1, 4]diazepines from o‐phenylenediamine derivatives and terminal alkynes using a Au(I)‐NHC‐complex‐catalyzed hydroamination/cyclization process.